An EOFs Study of Thermospheric Nitric Oxide Flux Based on TIEGCM simulations. Issue 11 (29th November 2019) - Li, Zheng; Knipp, Delores; Wang, Wenbin; Shi, Yining; Wang, Miao; Su, Ye; Li, Jingyuan
Abstract: The National Center for Atmospheric Research Thermosphere‐Ionosphere‐Electrodynamics General Circulation Model (TIEGCM) is a three‐dimensional physics model of the Earth's upper atmosphere. Using eigen analysis, the hourly NO infrared radiative flux (NOF) during 2002–2015 obtained from TIEGCM simulations are decomposed into four empirical orthogonal functions (EOFs). The first mode of variability is significantly associated with Kp and F10.7, implying that geomagnetic activity and solar extreme ultraviolet flux make a strong contribution to NOF variability. EOF 2 shows an antisymmetry between the northern and southern hemispheres and has a very strong correlation with the solar declination angle, suggesting that annual and seasonal variations of thermospheric temperature and composition play dominant roles in EOF 2. Lacking a strong correlation with solar and/or geomagnetic indices, EOF 3 may be associated with thermospheric circulation driven by the offsets between the geomagnetic and geographic poles. A strong correlation with Dst indicates that EOF 4 may be associated with geomagnetic activity and NO transport due to the enhanced meridional wind. Additionally, comparisons between TIEGCM EOFs and Sounding of the Atmosphere using Broadband Emission Radiometry EOFs are also included in our study. This work shows important features of TIEGCM via eigen analysis on NOF and suggests some model shortcomings through the results of model‐data comparison. Key Points: Using eigen analysis, the hourly NO infrared radiative flux during 2002–2015 obtained from TIEGCM simulations is decomposed into four EOFs Comparisons between TIEGCM EOFs and SABER EOFs are also included in our study